The relationship between tectonic stresses, joint patterns and landslides (Journal of Nepal Geological Society, 2006)
Tectonic stresses play a major role in the evolution of the present day landscape in the higher Himalayas. One of the principal geological manifestations of these stresses is the spatial orientation of joints and fractures. In this study these planar features and the stresses were correlated with landslides. It is observed that the direction of failure planes of landslides is concentrated either towards minimum stress axis s3 or along the intermediate stress axis s2 but never along the maximum stress axis s1. The results provide the first rational basis towards the relationship of stresses, joint patterns and landslides in the Himalaya and have laid the foundation for further work on the stress – magnitude relationship of landslides for the region.